Pengaruh Customer Intimacy, Customer Experience, Customer Satisfaction, dan Customer Bonding Terhadap Loyalitas Pelanggan - Siska Siska; Dian Nur Rahmawati; Ilham Ilham (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2023)
This study aims to determine the effect of customer intimacy, customer experience, customer satisfaction, and customer engagement on customer loyalty at the Haji Cilik shop in Tenggarong. The sample used was 105 respondents and used the sampling technique Random Sampling. This type of research is research with a quantitative approach. The research results show that the four variables, namely customer intimacy (X1), customer experience (X2), customer satisfaction (X3), and customer bonding (X4) simultaneously influence customer loyalty. Based on the partial test, the customer experience and customer bonding variables have a positive effect on customer loyalty because the calculation results show that t count > t table. Meanwhile, the variable customer intimacy and customer satisfaction partially do not have a significant effect on customer loyalty at the H. Cilik Shop in Tenggarong so that the second and fourth hypotheses are rejected. Furthermore, the research results also show that customer bonding is the variable that has the most dominant influence on customer loyalty. Customer bonding is one of the strategies that H. Cilik has to maintain long-term relationships with customers, namely a strategy that not only tries to satisfy its customers but also keeps them from turning to other companies by carrying out certain activities to bind their customers.